Effect of Workplace Violence Management Program on the Incidence - Sadatmahaleh, Masumeh Movaghari; Khoshknab, Masoud Fallahi; Rahguy, Abolfazl; Arsalani, Narges; Biglarian, Akbar (Advances in Nursing & Midwifery, 2018)
Introduction: Emergency nurses are at higher risk for workplace violence than other health care workers, so a workplace violence management program is crucial to prevent violence. Therefore, the purpose of the present study was to explore the effect of a workplace violence management program on the incidence of workplace violence against nurses in hospital emergency departments. Method: This study applied a quasi-experimental design using control groups and pre- and post-tests. The research units included 48 nurses working in the emergency departments of Farabi Hospital and Amir Alam Hospital in Tehran. The intervention included the use of a program featuring some management issues such as applying ventilation, using closed-circuit television cameras, modifying lightings, employing a security guard for the evening shift, and training. The training, which was entitled “Management and Prevention of Workplace Violence,” was implemented as a 2-day workshop using training programs. The data collection tool was the Workplace Violence in the Health Sector Questionnaire. Chi-square test and t-test were used to test the hypotheses. The data were analyzed using SPSS version 23. Results: The results of the study showed that the frequency of different forms of violence such as physical, psychological, sexual, and racial ones was decreased after the intervention, but this decrease was not statistically significant. Conclusion: The findings of the present study revealed that although the management program of preventing workplace violence with sub-categories such as training, security, physical environment, and policies and procedures could reduce the incidence of violence, this decrease was not significant; the lack of significance of the decrease was probably due to the low sample size and the short follow-up period (i.e., one month). Therefore, it is recommended that this study be carried out on a larger population with a longer follow-up period.